(untitled) (Journal of Nepal Geological Society, 2016)
Geological mapping is very important technique to predict geological condition for underground structures. It helps to construct geological model for site selection and designing of any underground structures. Geological uncertainty is directly proportional to the accuracy of geological mapping. More accurate geological mapping resulted fewer uncertainties. Precise delineation of faults, shear/weak zones and water bearing zones is important part of the geological mapping to predict uncertainties. Geological mapping to predict geological condition for underground structures is a challenge in the tectonically active Nepal Himalaya due to thrusting, faulting, folding and reverse metamorphism nature of rocks with difficult terrain and high overburden. The mapping for underground structures is mostly focus on rock mass properties, faults, weak/shear zones, fractured zone, joints, folds, weathering depth and ground water bearing zones. This paper highlights importance of geological mapping and challenges for underground structures with case studies of uncertainties faced due to poor geological mapping.